OP0215 Subcutaneous Abatacept in Patients with Polyarticular Juvenile Idiopathic Arthritis and Inadequate Response To Biologic or Non-Biologic Disease-Modifying Antirheumatic Drugs: Pharmacokinetics, Efficacy and Safety. (15th July 2016) - Ruperto, N.; Lovell, D.J.; Tzaribachev, N.; Vega-Cornejo, G.; Louw, I.; Berman, A.; Calvo, I.; Cuttica, R.; Horneff, G.; Avila-Zapata, F.; Anton, J.; Viola, D.; et al.
Abstract : Background: IV abatacept (ABA) 10 mg/kg every 4 weeks is safe and effective in reducing signs and symptoms of polyarticular forms of juvenile idiopathic arthritis (pJIA) in children and adolescents. 1 SC ABA 125 mg weekly has therapeutically equivalent efficacy and comparable safety to IV ABA in adult RA, but similar data in pJIA are lacking. Objectives: To assess the PK, efficacy and safety of SC ABA in children and adolescents with active pJIA. Methods: This single-arm, open-label (OL), Phase III study (NCT01844518 ) enrolled patients (pts) aged 2–17 years (yrs) with pJIA and an inadequate response/intolerance to ≥1 DMARD. Pts received SC ABA weekly OL for 4 months (M), based on body weight tier (10–<25 [50 mg ABA], 25–50 [87.5 mg ABA] and >50 kg [125 mg ABA]). JIAACR criteria 30 (JIAACR30) responders at 4M could enter a 20M OL extension; JIAACR30 non-responders could continue SC ABA for 3M more and discontinued if JIAACR30 was not achieved by M7. The primary endpoint was steady-state blood trough concentration (Cminss ) of ABA at 4M in the 6–17-yr-old pJIA pts (n=173); we report PK, efficacy and safety from the initial 4M OL phase for these pts. Results: Baseline characteristics of the 173 pJIA pts were: mean age (SD) =12.3 (3.1) yrs; mean number of active joints (SD) =12.4 (8.3); 78.6% of patients used MTX (mean dose: 12 mg/m 2 /week) and 26.6% failed prior biologic treatment. The target therapeutic Cminss of 10 μg/mL was achieved (Figure ); at 4M, mean (SD) Cminss was 42.1 (14.7) μg/mL and was consistent across all three weight groups. Robust JIAACR responses were seen at 4M (Figure ): JIAACR30, 80.9%; inactive disease, 29.5%. Biologic-naïve pts had a numerically higher JIAACR30 response than biologic-experienced pts at 4M. The number of pts with serious AEs and those who discontinued study drug due to AEs during the initial 4M were low (n=5 and n=3 [fatigue, exanthematous rash and ovarian germ cell teratoma] pts, respectively). AEs of interest reported included infections (31.8%) with 1 case of sepsis, injection-site reactions (5.2%) and malignancy (0.6%). No laboratory abnormalities or unexpected safety concerns were reported. Conclusions: The target therapeutic exposure for SC abatacept was achieved in pts aged 6–17 yrs with pJIA irrespective of weight group. The exposures for SC abatacept were within the range for IV abatacept in pJIA and comparable with SC abatacept in adult RA. Robust efficacy was observed with SC abatacept with no new safety concerns after 4M of treatment. References: Ruperto N, et al. Lancet 2008;372:383–91. Disclosure of Interest: N. Ruperto Grant/research support from: Gaslini Hospital, Bristol-Myers Squibb, Hoffman-La Roche, Janssen, Novartis, Pfizer, sanofi aventis, Schwarz Biosciences, Sobi, Consultant for: AbbVie, Amgen, Biogen Idec, Baxalta, Boehringer, Bristol-Myers Squibb, Celgene, EMD Serono, Hoffman-La Roche, Janssen, Novartis, Pfizer, Servier, Sinergie, Takeda, Speakers bureau: AbbVie, Amgen, Biogen Idec, Baxalta, Boehringer, Bristol-Myers Squibb, Celgene, EMD Serono, Hoffman-La Roche, Janssen, Novartis, Pfizer, Servier, Sinergie, Takeda, D. J. Lovell Grant/research support from: NIH, Consultant for: AstraZeneca, Bristol-Myers Squibb, AbbVie, Pfizer, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Biogen, Takeda, Genentech, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Janssen, N. Tzaribachev Grant/research support from: UCB, Pfizer, Janssen, Roche, G. Vega-Cornejo: None declared, I. Louw: None declared, A. Berman: None declared, I. Calvo Grant/research support from: Novartis, Speakers bureau: AbbVie, Roche, Novartis, Sobi, R. Cuttica: None declared, G. Horneff Grant/research support from: Pfizer, AbbVie, Roche, F. Avila-Zapata: None declared, J. Anton Grant/research support from: Pfizer, Novartis, Speakers bureau: Pfizer, AbbVie, Novartis, Sobi, Roche, D. Viola: None declared, I. Foeldvari: None declared, V. Keltsev: None declared, D. Kingsbury: None declared, X. Li Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Nys Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, R. Wong Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Martini Grant/research support from: The Gaslini Hospital, which is the public Hospital where I work as full time public employee, has received contributions from the following industries: Abbott, Bristol-Myers Squibb, "Francesco Angelini", GlaxoSmithKline, Hoffman-La Roche, Italfarmaco, Janssen, Novartis, Pfizer, sanofi aventis, Schwarz Biosciences, Sobi, Xoma, Wyeth, Consultant for: Abbott, AbbVie, Amgen, Biogen, Bristol-Myers Squibb, Astellas, Boehringer, Italfarmaco, Janssen, MedImmune, Novartis, NovoNordisk, H. I. Brunner Consultant for: Pfizer, Bristol-Myers Squibb, UCB, Janssen, Amgen, Celgene, AstraZeneca, Novartis, Genentech, Speakers bureau: Novartis, Genentech